DNA Barcoding and Atlantic reef fishes: The molecular identification of a reef fish community from the Todos os Santos Bay, Bahia, Brazil. (December 2017) - Duarte, L.A.G.; Oliveira, E.J.F.; Amorim, A.; Silva, D.A.; Carvalho, E.F.; Mazzoni, R.; Amaral, C.R.L.
Abstract: The reef fish community is one of the most explored fish stock by local and medium scale fishing activities as well as by the international ornamental fish trade. Despite these intense commercial activities, several reef species are poorly known. The reef fish community limited knowledge makes difficult the commercial regulation and also the adoption of conservation policies and general law enforcement. The present study deals with the molecular identification of a reef fish community from the Baía de Todos os Santos, Bahia, Brazil in order to construct a reference database for molecular identification of these species. We evaluated the molecular identification of 51 species included in 28 distinct families. The specimens were caught using freediving techniques and tissue samples were obtained from the epaxial musculature. The DNA barcoding methodology was used for the amplification of a 650 bp fragment from the mitochondrial COI gene. Among the 51 obtained COI sequences, 16 of them represent new record for the species in the Brazilian coastal region including two species ( Gramma brasiliensis and Scarus trispinosus ) without any sequencing data available until now.